2018
DOI: 10.3832/ifor2190-011
|View full text |Cite
|
Sign up to set email alerts
|

Tree biomass and carbon density estimation in the tropical dry forest of Southern Western Ghats, India

Abstract: United Nations Framework Convention on Climate Change highlights the significance of carbon storage and emission in forests towards climate change mitigation. The aim of this study was to quantify the tree biomass and carbon density (carbon storage) in the tropical dry forest of the Chinnar Wildlife Sanctuary of Kerala located in the Southern Western Ghats, India. We investigated the species-wise contribution of carbon (C) storage, as well as the species-wise and plot-wise correlation between carbon and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…This situation shows that the potential of timber forest products in these two subdistricts is still complete, where small to large diameters are still formed in this mixed natural forest structure. The reverse J-shaped curve in the graphs indicated that the forest had a more or less good condition (Myanmar 2016;Padmakumar et al 2018). Based on the distribution of the number of individuals per unit area of a hectare and diameter class for the two sub-districts, it can be seen that the number of individuals scattered in the two sub-districts did not experience a big difference (Figure 5).…”
Section: Potential Of Timber Productsmentioning
confidence: 94%
“…This situation shows that the potential of timber forest products in these two subdistricts is still complete, where small to large diameters are still formed in this mixed natural forest structure. The reverse J-shaped curve in the graphs indicated that the forest had a more or less good condition (Myanmar 2016;Padmakumar et al 2018). Based on the distribution of the number of individuals per unit area of a hectare and diameter class for the two sub-districts, it can be seen that the number of individuals scattered in the two sub-districts did not experience a big difference (Figure 5).…”
Section: Potential Of Timber Productsmentioning
confidence: 94%
“…The lower above-ground biomass stock recorded in the restored area can be attributed to the higher number of trees with larger diameter in the natural forest [71][72][73]. Usually, mature forests are characterized by old trees with higher diameter; trees in younger stands on the contrary have smaller diameters in restored forest [74]. The lower above-ground biomass in the semi-natural forest in comparison to the natural could be attributed mainly to anthropogenic disturbance such as logging and man-made wildfires in the area [28,29].…”
Section: Carbon Sequestration and Biomass Reclaimmentioning
confidence: 97%
“…Padmakumar et al . 37 assessed the tree C stocks of Chinnar Wildlife Sanctuary in Western Ghats and observed a strong positive relationship with basal area. There is a paucity of information regarding the ecosystem-level C stocks and their relationships with diversity {species richness, species evenness, Shannon’s diversity index and Simpson’s dominance index}, structural attributes {density, basal area, big-sized trees (≥ 60 cm DBH) and mean tree DBH} and environmental factors {elevation, mean annual precipitation (MAP), mean annual temperature (MAT), slope and aspect} in tropical forests of India, particularly in Western Ghats.…”
Section: Introductionmentioning
confidence: 99%